The Unseen Complexities of Digital Mental Health Services in Indonesia (COVID-19 Era): A Qualitative Study - Farah Diba Maharani; Dimitar Karadzhov (Jurnal Health Sains, 2026)
The COVID-19 pandemic accelerated the adoption of digital mental health services (DMHS) in Indonesia as an alternative approach to addressing limited access to conventional psychological services. However, the rapid implementation of these services also revealed various structural, technological, and regulatory challenges within Indonesia’s mental health system. This study aimed to explore stakeholders’ experiences in implementing DMHS during the COVID-19 era, including the challenges encountered, adaptive strategies employed, and recommendations for future service development. This research employed a qualitative exploratory design using semi-structured interviews involving 14 stakeholders, consisting of psychologists, platform managers, founders, and representatives of professional organizations in Indonesia. Data were collected through online interviews and analyzed using inductive thematic analysis supported by NVivo 14 software. The findings identified several major themes, including community and client readiness, service provider readiness, regulatory and legal conditions, technological limitations, service effectiveness and quality challenges, and capacity building and innovation. The study revealed that stigma, digital inequality, unclear regulations, and therapist burnout significantly affected the effectiveness of DMHS implementation. Nevertheless, stakeholders adopted adaptive strategies such as hybrid services, peer learning, structured evaluations, and digital innovation to maintain service quality. In conclusion, strengthening regulations, infrastructure, professional competence, and ethical standards is essential to ensure sustainable and effective digital mental health services in Indonesia.